Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

prove that a) sinx-cosx+1/sinx+cosx-1=secx+tanx b)if 2cosx+sinx=1,then find the value of 7cosx+6sinx c)find the values of xand y for which cosecA= x 2 -y 2 /x 2 +y 2 is satisfied

prove that
 a)      sinx-cosx+1/sinx+cosx-1=secx+tanx
b)if 2cosx+sinx=1,then find the value of 7cosx+6sinx
c)find the values of xand y for which cosecA=x2-y2/x2+y2is satisfied
 
 

Grade:12th pass

2 Answers

Arun
25763 Points
2 years ago
sinx-cosx+1/ sinx+cosx -1 =(sinx-cosx+1)x(sinx +cosx +1) / (sinx+cosx - 1)x(sinx +cosx +1) =(sinx +1)sq. - (cosx)sq./ (sinx +cosx) sq. - (1)sq. =sinsq.x+2sinx+1-cossq.x/ sinsq.x+cossq.x+2sinxcosx-1 =2sinsq.x+2sinx/ 2sinxcosx =2sinx(sinx +1)/ 2sinxcosx =sinx+1/cosx =(1+sinx)x(1-sinx)/ (cosx) x(1-sinx) =cosx/(1-sinx) (dividing num. and den. by cosx) =1/secx-tanx = sec x + tan x
Rishi Sharma
askIITians Faculty 646 Points
8 months ago
Dear Student,
Please find below the solution to your problem.

a) sinx-cosx+1/ sinx+cosx -1
= (sinx-cosx+1)x(sinx +cosx +1) / (sinx+cosx - 1)x(sinx +cosx +1)
= (sinx +1)sq. - (cosx)sq./ (sinx +cosx) sq. - (1)sq.
= sinsq.x + 2sinx + 1 – cossq.x / sinsq.x + cossq.x + 2sinxcosx – 1
= 2sinsq.x + 2sinx / 2sinxcosx
= 2sinx(sinx +1)/ 2sinxcosx
= sinx + 1/cosx
= (1+sinx)x(1-sinx)/ (cosx) x(1-sinx)
= cosx/(1-sinx) (dividing num. and den. by cosx)
= 1/secx-tanx
= sec x + tan x

(b) 645-2176_01.PNG
(c)
645-1317_01.PNG645-2366_01.PNG

Thanks and Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free